1975
DOI: 10.1136/jnnp.38.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Flaccid paraplegia: a feature of spinal cord lesions in Holmes-Adie syndrome and tabes dorsalis.

Abstract: SYNOPSIS In a patient with Holmes-Adie syndrome, and in another with tabes dorsalis, a transverse cord lesion resulted in a severe, but flaccid paraplegia with absent tendon reflexes. Flexor spasms were severe in both patients, but spasticity was absent. The significance of these observations is discussed in relation to the functional and anatomical disorder in these two syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In a minority of cases, flaccidity persists chronically after occurrence of a central lesion, e.g., with some spinal cord infarcts25, 132, 193 or cerebral lesions 177. Persistent flaccidity is often associated with a greater degree of paresis and poorer outcome,36, 79, 82, 133, 177, 197, 221 although this is not always the case 159, 201. Occasionally, a secondary reduction of spasticity is also observed months after spinal cord injury, which may suggest secondary impairment or degeneration of premotor neuronal circuits or of motor neurons 108…”
Section: Immediate Effects Of Central Lesionmentioning
confidence: 99%
“…In a minority of cases, flaccidity persists chronically after occurrence of a central lesion, e.g., with some spinal cord infarcts25, 132, 193 or cerebral lesions 177. Persistent flaccidity is often associated with a greater degree of paresis and poorer outcome,36, 79, 82, 133, 177, 197, 221 although this is not always the case 159, 201. Occasionally, a secondary reduction of spasticity is also observed months after spinal cord injury, which may suggest secondary impairment or degeneration of premotor neuronal circuits or of motor neurons 108…”
Section: Immediate Effects Of Central Lesionmentioning
confidence: 99%
“…3,4 Other forms of spinal cord involvement in syphilis have also been described. 5,6 We describe the magnetic resonance imaging (MRI) findings in a patient with tabes dorsalis. These neuroimaging abnormalities have not yet been described in the literature to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also reported on the histology of the rest of the nervous system, suggesting that the areflexia was due to selective degeneration of neurones in the dorsal root ganglia, possibly supplying the muscle spindles. The pathophysiology of the reflex changes is discussed in Harriman and Garland (1968) and Swash and Earl (1975).…”
Section: Discussionmentioning
confidence: 99%